Corrigendum to âA comprehensive review of experimental studies of nanoparticles-stabilized foam for enhanced oil recoveryâ (Journal of Petroleum Science and Engineering (2018) 164 (43â74), (S0920410518300445) (10.1016/j.petrol.2018.01.035)) - Yekeen, N. (2019)
The authors of âA comprehensive review of experimental studies of nanoparticles-stabilized foam for enhanced oil recoveryâ (Journal of Petroleum Science and Engineering 164 (2018) 43â74) have overlooked errors in Table 2 and reference during the proofreading process. The work of Arthur Uno Rognmo and its co-researchers titled âNanotechnology for improved CO 2 utilization in CCS: Laboratory study of CO 2 -foam flow and silica nanoparticle retention in porous mediaâ (https://doi.org/10.1016/j.ijggc.2017.07.010) cited in Table 2 was not included in the reference list. Also, the experiment referred was performed at 90 bar, not âroom pressureâ as listed in Table 2. The corrections to the references which has been missed in the article is given below: Â© 2018 Elsevier B.V.